An expanded circumscription of Trichocentrum (Orchidaceae: Oncidiinae) to include Grandiphyllum and Saundersia - Meneguzzo, Thiago E. C.; Chase, Mark W. (Phytotaxa, 2024)
The genus Trichocentrum is again expanded, this time to include Grandiphyllum and Saundersia, and the respective combinations are made.